2013
DOI: 10.1159/000353541
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Chinese Version of Addenbrooke's Cognitive Examination-Revised for Screening Mild Alzheimer's Disease and Mild Cognitive Impairment

Abstract: Background/Aims: As a suitable test to screen for Alzheimer's disease (AD) or mild cognitive impairment (MCI), studies to validate the Chinese version of Addenbrooke's Cognitive Examination-Revised (ACE-R) are rare. Methods: A total of 151 subjects were recruited and the neuropsychological assessments were employed. One-way analysis of variance and Bonferroni correction were used to compare scores of different psychometric scales. Intraclass correlation coefficient (ICC) and Cronbach's coefficient α were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 67 publications
8
48
1
2
Order By: Relevance
“…However, the cutoff point was lower in a UK memory clinic with patients aged 75-85 years (81/100) [23], and even lower in our previous study in Spain (65/100) in a population with a mean age of 78 years and a mean number of years of education of 7.4 as well as different types of dementia [4]. Similar discrepancies were observed in the previous versions of the ACE [24,25,26]. In this regard, the implementation of the current norms to the sample of healthy controls and patients with mild dementia of different types used in our previous study of validation of the ACE-III [4] demonstrated an improvement of the accuracy for the discrimination between healthy and cognitively impaired individuals.…”
Section: Discussionsupporting
confidence: 60%
“…However, the cutoff point was lower in a UK memory clinic with patients aged 75-85 years (81/100) [23], and even lower in our previous study in Spain (65/100) in a population with a mean age of 78 years and a mean number of years of education of 7.4 as well as different types of dementia [4]. Similar discrepancies were observed in the previous versions of the ACE [24,25,26]. In this regard, the implementation of the current norms to the sample of healthy controls and patients with mild dementia of different types used in our previous study of validation of the ACE-III [4] demonstrated an improvement of the accuracy for the discrimination between healthy and cognitively impaired individuals.…”
Section: Discussionsupporting
confidence: 60%
“…We followed the criteria proposed by Petersen [13, 28, 29] (significant impairment of the patient and/or caregiver’s report, objective evidence of memory decline compared to equivalent controls for age, sex, and years of schooling; Clinical Dementia Rating Scale [CDR] score equal to 0.5 and preservation of activities of daily living).…”
Section: Methods and Subjectsmentioning
confidence: 99%
“…This is an important limitation if we consider that previous studies showed that the annual conversion rate from MCI to Alzheimer disease (AD) was 10–15%, and approximately 50% of MCI patients will convert to AD within 4 years [6]. Therefore, MCI is considered to be a transition phase from normal aging to AD, and its precise detection allows to initiate early treatment [13]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations